Cooperative learning and students’ interest in learning biology - Khairina Afni; Dewi Rulia Sitepu (Institute of Information Technology and Social Science (IITSS), 2025)
This research aimed to observe cooperative learning and biology learning interest of MA Aisyiyah Binjai City students. This study used quantitative research. The sample in this study were 26 students of class X-A MA Aisyiyah Binjai City and 1 biology teacher. The research instruments were a questionnaire on learning interest in biology subjects and with a biology teacher. Based on the research and data analysis, the highest percentage of scores for the indicators in the questionnaire statement was 30.1% for attention to biology subjects, indicating a high category. Therefore, it can be concluded that cooperative learning and biology learning interests of MA Aisyiyah Binjai City students were running well.